Membangun Etika dan Karakter pada Siswa SD di Desa Wanajaya melalui Kegiatan Edukasi - Kurniaji, Kalfajrin; Alifa Zahra, Restu; Daffa Amanda, Hafizha (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2025)
Elementary school education has an important role in the formation of individual ethics and character. In Wanajaya Village at SDN 1 Cipatat and SDN 2 Cipatat, the author identified problems regarding the process of developing students' ethics and character. This is caused by the lack of access for educators to educational materials. Students also have the freedom to access the internet via smartphone without parental supervision, thus making the situation worse. This is a concern for the author which requires intervention through educational programs. This program aims to provide students with an in-depth understanding of moral and ethical values ​​through interactive lecture methods, providing real examples and reflection. Collaboration between teachers, parents and the surrounding community is a crucial factor in creating a conducive learning environment. By implementing this education, ethics and character program, students are expected to not only excel academically, but also have good morals and ethics, in accordance with the national education vision which includes cognitive, affective and psychomotor aspects. It is hoped that this program can become a model for other villages with similar challenges, and ongoing evaluation will ensure its effectiveness in the long term